EFAS Score – Multilingual Development and Validation of a Patient-Reported Outcome Measure (PROM) by the Score Committee of the European Foot and Ankle Society (EFAS). Issue 4 (16th October 2019) - Richter, Martinus; Agren, Per-Henrik; Besse, Jean-Luc; Cöster, Maria; Kofoed, Hakon; Maffulli, Nicola; Rosenbaum, Dieter; Steultjens, Martijn; Alvarez, Fernando; Boszczyk, Andrzej; Buedts, Kristian; Guelfi, Marco; et al.
Category: Basic Sciences/Biologics Introduction/Purpose: A scientifically sound validated foot and ankle specific outcome measure for different European languages is still missing. Indeed, language-specific cross cultural validation in other languages than English is largely absent. Some outcome measures were validated for specific pathologies such as hallux valgus, ankle arthritis or flatfoot. The European Foot and Ankle Society (EFAS) established in 2013 a Score Committee to develop, validate, and publish a new score, the "EFAS Score", which is not specific for single pathologies for different European languages. The principal aim of this project was to develop and validate the EFAS Score simultaneously for different European languages. Methods: The EFAS Score was developed and validated in three stages: 1) item (question) identification, 2) item reduction and scale exploration, 3) confirmatory analyses and responsiveness. The following score specifications were chosen: scale/subscale (Likert 0-4), questionnaire based, outcome measure, patient related outcome measurement. For stage 3, data were collected pre- operatively and post-operatively at a minimum follow-up of 3 months and mean follow-up of 6 months. Item reduction, scale exploration, confirmatory analyses and responsiveness were executed using analyses from classical test theory and item response theory. Results: Stage 1 resulted in 31 general and 7 sports related questions. In Stage 2, a 6-item general EFAS Score was constructed using English, German, French and Swedish language data. In Stage 3, internal consistency of the scale was confirmed in seven languages: the original four languages, plus Dutch, Italian and Polish (Cronbach's Alpha >0.86 in all language versions). Responsiveness was good, with moderate to large effect sizes in all languages, and significant positive association between the EFAS Score and patient-reported improvement. No sound EFAS Sports Score could be constructed. Conclusion: The multi-language EFAS Score has been successfully validated for orthopaedic foot and ankle surgery populations incorporating a wide variety of foot and ankle pathologies, including language-specific validation in seven languages so far (English, German, French, Swedish, Dutch, Italian, Polish). Validation for other languages (Danish, Finnish, Norwegian, Portuguese, Spanish, Turkish) is in progress. All validated score versions are freely available atwww.efas.co .